в1=х-8
в2=3х
в3=6х
в3=в2*q
q=в3/в2=6х/3х=2
в2=в1*2
3х=(х-8)*2
3х=2х-16
х= -16 Это ответ.
Проверка:
в1=-16 - 8= -24
в2= -24*2= -48; 3х= -48
в3= -48*2= -96; 6х= -16*6= 96. Все сходится.
ответ: -16.
Пошаговое объяснение: так как прогрессия геометрическая, то 6х:3х = 3х: ( х-8). 6х:3х=2, то 3х÷ (х -8 )=2, решаем уравнение. 3х = 2(х -8), 3х=2х-16, 3х- 2х=-16, х= -16
в1=х-8
в2=3х
в3=6х
в3=в2*q
q=в3/в2=6х/3х=2
в2=в1*2
3х=(х-8)*2
3х=2х-16
х= -16 Это ответ.
Проверка:
в1=-16 - 8= -24
в2= -24*2= -48; 3х= -48
в3= -48*2= -96; 6х= -16*6= 96. Все сходится.
ответ: -16.
Пошаговое объяснение: так как прогрессия геометрическая, то 6х:3х = 3х: ( х-8). 6х:3х=2, то 3х÷ (х -8 )=2, решаем уравнение. 3х = 2(х -8), 3х=2х-16, 3х- 2х=-16, х= -16